Karnataka Draft Annual Plan 1983-84 Part-II-Statements Government of Karnataka Planning Department - Planning Commission (Planning Commission, 1983)
State plan outlay under scp physical targets under scp: scp-2 20 point programme outlay and expenditure : tpp-1 statement 20 point programme physical targets and achievements: tpp-2 statement employment content of sectoral programmes-outlay and expenditure : emp-1 statement employment content of sectoral programmes-targets and achievements : emp-2 statement state plan outlay and disaggregated outlay for district: dp-1 statement outlay of district sector programmes : dp-2 statement
Government of Karnataka Planning Department